Grit or Honesty-Humility? New Insights into the Moderating Role of Personality between the Health Impairment Process and Counterproductive Work Behavior - Ceschi, Andrea; Sartori, Riccardo; Dickert, Stephan; Costantini, Arianna (Frontiers in Psychology, 2016)
It is acknowledged that chronic job demands may be depleting workers’ stamina resulting in burnout conditions and ultimately causing further health problems. This relation, known as health impairment process, has recently been considered as a possible explanation for the emergence of counterproductive work behavior (CWB). The present work aims to examine the role of two personality traits (i.e., Grit and Honesty–Humility) in this process. The results, based on a sample of 208 private service sector employees, confirm the presence of a fully mediated process and show how Honesty–Humility positively moderates the relationship between job demands and exhaustion, whereas Grit has a negative effect on the relation between exhaustion and CWB. Implications for assessment procedure and hiring decisions are discussed.